Proteomics of Urinary Extracellular Vesicles Highlight the Involvement of Vitronectin and the Fibrinolytic and TNF Pathways as Mechanisms Underlying Renal Fibrosis in Kidney Transplant Patients - Marta Clos‐Sansalvador; Sergio G. Garcia; Paula Rodríguez‐Martínez; Marta Sanroque‐Muñoz; Miriam Font‐Morón; Cristina Grange; Benedetta Bussolati; Marcella Franquesa; Javier Juega; Francesc E. Borràs (Journal of Extracellular Biology)
ABSTRACT Vitronectin (VTN) is a potential non‐invasive biomarker for renal fibrosis, originally described in urinary extracellular vesicles (uEV) from kidney transplant patients (KTx). However, VTN's specific role in renal fibrosis is unclear, as it is involved in various physiological processes. This study aims to identify other uEV‐associated proteins linked to renal fibrosis to clarify which pathways involve VTN. uEV were isolated from 33 KTx patients and five healthy controls. uEV proteins were analysed using proximity extension assay (PEA), and data were normalized and compared using Welch's two‐sided t‐test to identify differentially expressed proteins between fibrotic (n = 31) and non‐fibrotic patients (n = 7). Urinary VTN levels and monocyte chemoattractant protein‐1 (MCP‐1) were measured by ELISA. PEA analysis identified 33 proteins overexpressed in the fibrotic group. These proteins clustered in STRING analysis, primarily associating with coagulation, fibrinolysis and TNF‐inflammation involving macrophages. ELISA detection of MCP‐1 further validated the results. High levels of VTN in the fibrotic group were accompanied by the upregulation of fibrinolytic pathway components (PAI‐1, tPA and uPAR), which are well‐known to interact with VTN. This study highlights TNF‐induced inflammation involving macrophages and fibrinolysis as key mechanisms underlying renal fibrosis with direct implications of VTN, which support VTN's potential as a biomarker for this pathological process.